2009
DOI: 10.1103/physrevb.80.174427
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high-Tcferromagnetism inZnx(ZnO)

Abstract: Zn x ͑ZnO͒ 1−x granular films with nominal atomic concentration of x =0ϳ 1 were prepared by magnetron cosputtering method. Ferromagnetism is observed in films with 0.04Յ x Ͻ 0.60. The room-temperature saturated magnetization increases with increasing x and reaches its maximum value of about 3.34 emu/cc at x = 0.31. The temperature-dependent magnetization curve could be fitted within the framework of Stoner model in a large temperature range from 50 to 800 K. The obtained Curie temperature is higher than 500°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It is worth pointing out that the maximum magnetization of the nanoparticles is obviously independent from their average particle size and ZnO content. The highest room temperature saturation magnetization obtained in this study was 0.27 emu/g (Z17), which was found to be a higher value in comparison to the literature one (from 6 × 10 -4 to 6 × 10 -3 emu/g) for non-doped ZnO nanoparticles of various sizes in the range of 4-500 nm [19,22,26,39,45,[73][74][75]. Higher values of up to 0.62 emu/g were reported for the ZnO nanofilms, but significant error was obviously possible in the thin films masses determination.…”
Section: Magnetic Measurementsmentioning
confidence: 38%
See 1 more Smart Citation
“…It is worth pointing out that the maximum magnetization of the nanoparticles is obviously independent from their average particle size and ZnO content. The highest room temperature saturation magnetization obtained in this study was 0.27 emu/g (Z17), which was found to be a higher value in comparison to the literature one (from 6 × 10 -4 to 6 × 10 -3 emu/g) for non-doped ZnO nanoparticles of various sizes in the range of 4-500 nm [19,22,26,39,45,[73][74][75]. Higher values of up to 0.62 emu/g were reported for the ZnO nanofilms, but significant error was obviously possible in the thin films masses determination.…”
Section: Magnetic Measurementsmentioning
confidence: 38%
“…The existance of RFTM in the undoped ZnO stimulated discussion about the role of intrinsic defects in this phenomenon. For the Zn-O system, also known as a pristine oxide, it was shown that defects, such as Zn and O vacancies [16][17][18][19][20][21], Zn interstitials [22], grain boundaries [23] and lattice distortions [24], might contribute to the development of RTFM. If all these defects are indeed responsible for the ferromagnetism in thin films and nanoparticles, they should be thermodynamically stable at least to room temperature, and magnetic exchange interaction between them should be strong enough for the existence of ferromagnetism to be feasible [25].…”
Section: Introductionmentioning
confidence: 99%
“…This shows how subtle the search for magnetism in these materials can be and the role of intrinsic or extrinsic defects, if any, has not been thoroughly established. Added to this, there are other claims of RT ferromagnetism in pure ZnO induced from intrinsic defects [16][17][18][19][20][21]. So it is essential that one pays special care for characterizing the samples in order to avoid any biased conclusions.…”
Section: Introductionmentioning
confidence: 96%
“…Diluted magnetic semiconductors (DMS) have been recently intensively studied for spintronic applications (Bonanni and Dietl, 2010;Ueda et al, 2001) and ZnCoO focuses a great part of attention here (Khare et al, 2006;Assadi et al, 2009;De Carvalho et al, 2010;Zhang et al, 2009;Gilliland et al, 2010). This is possible because high cobalt concentration in ZnO is expected due to the nearly identical Co 2 þ and Zn 2 þ ionic radii.…”
Section: Introductionmentioning
confidence: 98%